Refractive Regression and Changes in Central Corneal Thickness Three Years after Laser-Assisted Subepithelial Keratectomy for High Myopia in Eyes with Thin Corneas: A Retrospective Study. (3rd September 2017) - Fu, Dan; Zhang, Zhen-Yong; Wang, Lin; Zhou, Xing-Tao; Yu, Zhi-Qiang
ABSTRACT: This retrospective study aimed to explore refractive regression and central corneal thickness (CCT) following laser-assisted subepithelial keratectomy (LASEK) performed for the correction of high myopia in eyes with thin corneas. Forty patients (19 male, 21 female; mean age, 28.5 years) representing 76 treated eyes were included. The mean optical zone was 6.10 ± 0.32 mm, and the mean ablation depth was 121.53 ± 15.48 µm. CCT was significantly greater three years after surgery than at three months after surgery (425.66 ± 15.44 vs. 385.20 ± 12.81, respectively; p<0.001). The mean change in CCT from three months to three years was 40.46 ± 14.02 µm. The SE at three years was greater than that at three months (p<0.001). Although there was refractive regression, these data suggest that LASEK may have utility in the correction of high myopia in eyes with thin corneas.